Drill-String Vibration Suppression Using Hybrid Magnetorheological Elastomer-Fluid Absorbers - Jasem M. Kamel; Asan G. A. Muthalif; Abdulazim H. Falah (Actuators)
Rotary drilling systems with PDC bits, commonly used for drilling deep wells in the production and exploration of oil and natural gas, frequently encounter severe vibrations. These vibrations can cause significant damage to the drilling system, particularly its downhole components, leading to drilling performance inefficiencies, notably reducing the rate of penetration and incurring high costs. This paper presents a parametric study on a proposed new axial semi-active tool designed to mitigate these unwanted vibrations. The tool, an axial absorber with tunable stiffness and damping coefficients over a wide range, composed of a hybrid magnetorheological elastomer-fluid (MRE-F), is installed above the PDC bit. In this study, the lumped parameter model considering axial and torsional vibrations is followed to assess the effectiveness of including the proposed absorber in the drill-string system’s behavior and to estimate the optimal coefficient values for achieving high-efficiency drilling. The drilling system response shown in this study indicates that, with optimal axial absorber coefficient values, the bit dynamically stabilizes, and unwanted vibrations are minimized, effectively eliminating the occurrence of bit-bounce and stick–slip, even when operating at critical frequencies. The proposed semi-active control tool has been proven to significantly reduce maintenance time, reduce the costs associated with severe vibrations, extend the lifespan of bottom-hole assembly components, and achieve smoother drilling with a simple addition to the drilling system.